2018
DOI: 10.1007/s11910-018-0911-x
|View full text |Cite
|
Sign up to set email alerts
|

Principles of OCTA and Applications in Clinical Neurology

Abstract: Purpose of ReviewThe article reviews the recent findings on the use of optical coherence tomography angiography (OCTA) in neurology.Recent FindingsOCTA is a new addition to the powerful and complementary technology of the OCT. Due to its noninvasiveness, and reproducibility, it is possible to obtain high-resolution 3D images of the vessels of the human eye. As the vessels of the retina with the presence of endothelial cell’s tight junctions resemble the brain vessels, it was hypothesized that the imaging of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 83 publications
0
48
0
2
Order By: Relevance
“…; Teper et al. ; Wylęgała ) reported a significant difference between FAZ in the superficial and deep plexus; however, this finding may not be meaningful as Campbell et al. showed that all the vascular layers merged into one to create a single FAZ.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…; Teper et al. ; Wylęgała ) reported a significant difference between FAZ in the superficial and deep plexus; however, this finding may not be meaningful as Campbell et al. showed that all the vascular layers merged into one to create a single FAZ.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, several OCT devices with dyeless angiography modality are available; they differ in the use of algorithms, OCT technology and nomenclature (Wylęgała ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some OCT systems use swept-source technology featuring lower resolution but faster acquisition rate [13]. Others relay on spectral domain producing a smaller acquisition window but with a higher image quality [14]. The biggest advantage of AS-OCT over a Scheimpflug based system is that the numeric values are accompanied by the presence of high quality images that are superior in terms of resolution [15].…”
Section: Discussionmentioning
confidence: 99%